2016
DOI: 10.1111/inm.12298
|View full text |Cite
|
Sign up to set email alerts
|

Empathic processes during nurse–consumer conflict situations in psychiatric inpatient units: A qualitative study

Abstract: Empathy is a central component of nurse-consumer relationships. In the present study, we investigated how empathy is developed and maintained when there is conflict between nurses and consumers, and the ways in which empathy can be used to achieve positive outcomes. Through semistructured interviews, mental health nurses (n = 13) and consumers in recovery (n = 7) reflected on a specific conflict situation where they had experienced empathy, as well as how empathy contributed more generally to working with nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(147 citation statements)
references
References 69 publications
(103 reference statements)
3
124
0
4
Order By: Relevance
“…This is consistent with previous findings that restraint 'spoils the job' (Bigwood & Crowe 2008), and that mental health nurses experience tension in balancing their therapeutic role and the provision of empathic care with the potentially incompatible duty of managing risk to ensure safety (e.g. Bigwood & Crowe 2008;Gerace et al 2016). As with previous research (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous findings that restraint 'spoils the job' (Bigwood & Crowe 2008), and that mental health nurses experience tension in balancing their therapeutic role and the provision of empathic care with the potentially incompatible duty of managing risk to ensure safety (e.g. Bigwood & Crowe 2008;Gerace et al 2016). As with previous research (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is tension in mental health care between this desire to reduce restraint and the need to provide and maintain a safe environment, which is recognized as central to the therapeutic milieu of mental health inpatient wards (e.g. Gerace et al 2016;Hopkins et al 2009;Muir-Cochrane et al 2013). Other barriers to the reduction of restraint also exist; for example, staff attitudes, patient acuity, and ward factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses, such as the one quoted at the start of this paper, report that these tasks place demands on their time, consequently impacting relationship building (Harris & Panozzo, ; Perraud et al, ). It has also been identified that nurses may create a bubble around themselves to protect themselves from the stress of balancing the emotional needs of patients and other demands of practice, such as documentation and paperwork, resulting in lack of attention to the patient (Gerace et al, ).…”
Section: Barriersmentioning
confidence: 99%
“…), and nurses trying to understand the other person's perspective (Gerace et al . ). This indicates that mental health nurses should consider what can enable nurse self‐reflection and time spent together as a foundation for recovery during inpatient care.…”
Section: Discussionmentioning
confidence: 97%